2021
DOI: 10.1029/2021jb022755
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Bulk Flow Characteristics of Debris Flows Using Their High Frequency Seismic Signature

Abstract: Quantifying debris‐flow characteristics remains a key challenge in natural hazard research. Recent studies suggest that seismic signals can reveal debris‐flow properties. However, the accuracy and applicability of theoretical models linking bulk flow properties to the seismic signature of a debris flow remain elusive. By extending a previously proposed model of random single‐particle impact forces to multi‐particle force chains acting on the channel bed, we describe the generation of high frequency seismic sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 56 publications
(160 reference statements)
3
30
0
1
Order By: Relevance
“…Based on presented results and taking into account previous models and experiments, we propose a decoupled source mechanism for seismic and infrasound radiation by the flow, with the two wavefields being generated by different processes acting at the ground and at the flow surface respectively. Results agree with previous models and observation of seismic energy radiation by rivers (Burtin et al., 2008; Schmandt et al., 2013; Tsai et al., 2012) and debris flows (Burtin et al., 2009; Kean et al., 2015; Lai et al., 2018; Zhang, Walter, McArdell, de Haas, et al., 2021), indicating that seismic waves are generated by solid particle collisions and friction with the riverbed and banks and by fluid dynamic structures.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Based on presented results and taking into account previous models and experiments, we propose a decoupled source mechanism for seismic and infrasound radiation by the flow, with the two wavefields being generated by different processes acting at the ground and at the flow surface respectively. Results agree with previous models and observation of seismic energy radiation by rivers (Burtin et al., 2008; Schmandt et al., 2013; Tsai et al., 2012) and debris flows (Burtin et al., 2009; Kean et al., 2015; Lai et al., 2018; Zhang, Walter, McArdell, de Haas, et al., 2021), indicating that seismic waves are generated by solid particle collisions and friction with the riverbed and banks and by fluid dynamic structures.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the analysis of the seismic-acoustic radiation would require locating the radiating source. However, many studies have shown that the flow front dominates the generated seismic signal (Coviello et al, 2019;Zhang, Walter, McArdell, de Haas et al, 2021;, while for infrasound Marchetti et al (2019) found that the maximum signal amplitude is generated when the barycentre of the extended source representing the flow is located at the minimum distance to the infrasonic sensor. Therefore, we believe that our comparison between the seismic and infrasonic signal as a whole and the hydraulic data is permissible, since the velocity is actually the front velocity, and the maximum depth is measured in correspondence of the flow front (Pierson, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations